2022
DOI: 10.1021/acsomega.2c05625
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan-Grafted Polyacrylic Acid-Doped Copper Oxide Nanoflakes Used as a Potential Dye Degrader and Antibacterial Agent: In Silico Molecular Docking Analysis

Abstract: This study examined the catalytic and bactericidal properties of polymer-doped copper oxide (CuO). For this purpose, a facile co-precipitation method was used to synthesize CuO nanostructures doped with CS-g-PAA. Various concentrations (2, 4, and 6%) of dopants were systematically incorporated into a fixed amount of CuO. The prepared samples were analyzed by different optical, structural, and morphological characterizations. Field emission scanning electron microscopy and transmission electron microscopy micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 95 publications
(167 reference statements)
1
10
0
Order By: Relevance
“…This investigation (Figure c) indicated that the TOC of produced compounds under visible light irradiation decreased steadily with reaction time, and a considerable quantity of mineralization of dye was noticed after 150 min in Fe (6 wt %)-doped CdO. Moreover, results suggest that the dye may undergo a series of intermediate transformations before its deterioration ultimately leads to its complete mineralization. , The comparison of the current work with the literature, in terms of photocatalytic activity and reaction time is shown in Table .…”
Section: Resultsmentioning
confidence: 55%
“…This investigation (Figure c) indicated that the TOC of produced compounds under visible light irradiation decreased steadily with reaction time, and a considerable quantity of mineralization of dye was noticed after 150 min in Fe (6 wt %)-doped CdO. Moreover, results suggest that the dye may undergo a series of intermediate transformations before its deterioration ultimately leads to its complete mineralization. , The comparison of the current work with the literature, in terms of photocatalytic activity and reaction time is shown in Table .…”
Section: Resultsmentioning
confidence: 55%
“…This allowed us to calculate the rate constant represented in Figure 6a− suggest that the dye may undergo a series of intermediate transformations before its deterioration ultimately leads to its complete mineralization. 65,66 The bactericidal effectiveness of bare Fe 2 O 3 , St/Fe 2 O 3 , and (2, 4 wt %) Sr/St-doped Fe 2 O 3 NSs was obtained from inhibition zone measurements via an agar-well diffusion assay for S. aureus (G +ve) and E. coli (G −ve) as mentioned in Table 2. Specific concentrations (1.0 mg/50 μL and 0.5 mg/50 μL) of bare and Sr/St-Fe 2 O 3 NSs were filled in concerning wells, and CF (0.05 mg/50 μL) was utilized as a positive control for the comparison; meanwhile, DI water (50 μL) was used as the negative control.…”
Section: Resultsmentioning
confidence: 99%
“…This investigation (Figure ) indicated that the TOC of produced compounds under visible light irradiation decreased steadily with reaction time, and a considerable quantity of mineralization of dye was noticed after 180 min in Sr/St-Fe 2 O 3 (4%). Moreover, results suggest that the dye may undergo a series of intermediate transformations before its deterioration ultimately leads to its complete mineralization. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The prominent peaks at 603 and 524 cm −1 manifested the presence of Cu-O stretching vibrations. 52 Tauc plot. The UV-visible spectra of CuO NPs were analyzed to determine the band gap value.…”
Section: Characterization Techniquesmentioning
confidence: 99%